Ochrona interesu indywidualnego w postępowaniu administracyjnym dotyczącym lokalizacji i budowy dróg publicznych - na podstawie przepisów tzw. specustawy drogowej - Peljan, Michał (My University, 2015)
Budowa dróg publicznych, co do zasady wiąże się z koniecznością daleko idących ingerencji w prawa majątkowe jednostek. Wynika to z oczywistego faktu, że zarówno Skarb Państwa, jak również jednostki samorządu terytorialnego odpowiedzialne za realizację zadań publicznych nie dysponują wystarczającym zasobem nieruchomości dla realizacji pełnej sieci drogowej. Inwestycje infrastrukturalne są najczęściej podejmowane i realizowane w celach związanych z zaspokojeniem interesu publicznego, w tym w szczególności w celu zapewnienia należytego bezpieczeństwa użytkownikom dróg oraz możliwości szybkiego i sprawnego poruszania się, co w efekcie powinno przyczyniać się do szeroko rozumianego rozwoju społecznego oraz gospodarczego. W opisanych okolicznościach postępowania administracyjne związane z budową dróg publicznych prowadzą zwyczajowo do konfliktu pomiędzy interesem publicznym, a interesem indywidualnym. Żaden z przepisów ustaw dotyczących procesu inwestycyjnego, w tym również przepisy specustawy drogowej nie formułuje zasady nadrzędności interesu osób trzecich nad interesem publicznym, czy też interesem inwestora. Konflikt pomiędzy poszczególnymi kategoriami interesów należy rozstrzygać z zastosowaniem standardów konstytucyjnych, w tym w szczególności z uwzględnieniem zasady proporcjonalności oraz równości wobec prawa. Szczególne cele związane z budową dróg publicznych mogą stanowić uzasadnienie dla dokonywania ingerencji w prawa majątkowe jednostek, jednakże nie mogą prowadzić do całkowitego pozbawienia tych jednostek ochrony prawnej. Przepisy specustawy drogowej w przeważającej mierze spełniają konstytucyjne standardy ochrony praw majątkowych. Natomiast negatywnie należy ocenić w szczególności brak należytej ochrony interesów osób, których nieruchomości znajdują się poza pasem drogowym wyznaczonym w decyzji ZRiD.

In the content of the PhD thesis regulations of the so called Road Special Act (the act on specific rules concerning preparation and performance of national road investment on the 10th of April 2003) have been analyzed by taking into consideration assessing the conformity with Polish Constitution. The conducted research led to the following conclusions: 1.None of the provisions of acts concerning the investment process, including the provisions of the Special Road Act, formulate the principle of supremacy of third party interest over the public interest or the investor’s interest. The conflict between particular categories of interests should be resolved by application of constitutional standards, particularly the principle of proportionality and the principle of equality before the law. Specific aims connected with construction of public roads can provide justification for interference with individual property rights. However, they cannot lead to complete deprivation of legal protection of individuals. 2.Standards of constitutional protection of individual interest, particularly connected with protection against dispossession are similar under Polish legal provisions and under German Constitution. Simultaneously, special acts applied in Germany provide better legal protection before expropriation for the purposes connected with public roads construction (than Special Road Act). 3.The overwhelming majority of the Special Road Act provisions meet the constitutional standards of the property rights protection. On the other hand, the lack of proper protection of the interest of people, who own properties outside of the road zone specified in the decision on the performance permit concerning the road investment, should be judged unfavorably. 4. Compensation for real estate expropriated for public roads purposes (under regulations of the Special Road Act) states the so called fair compensation in the meaning of article 21 of Polish Constitution. 5. Regulations contained in the Road Special Act meet the constitutional standards of protection stemming from articles 45 (the right to the court) and 78 of the Polish Constitution (the right to challenge administrative decision). 6. The right to demand the return of the dispossessed property (that has not been used for public purposes) seems to find protection in the wording of the article 21 section 2 of the Polish Constitution. The claim for return of the property expires if the status of the public road is assigned to the property.
Protection of individual interests during administrative proceedings concerning location and construction of public roads - based on the provisions of the so called Road Special Act
Wydział Prawa i Administracji
Keywords: specustawa drogowa; road Special Act; drogi publiczne; public roads; wywłaszczenie; compulsory purchase; interes indywidualny; individual interest; interes publiczny; public interest